2021
DOI: 10.1177/0272989x20985836
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Advance Care Planning Videos for Patients: A Randomized Controlled Trial in Cancer, Heart, and Kidney Failure Outpatient Settings

Abstract: Background Patient videos about advance care planning (ACP; hereafter “Videos”), were developed to support uptake of provincial policy and address the complexity of patients’ decision-making process. We evaluate self-administered ACP Videos, compare the studies’ choice of outcomes, show correlations between the patients’ ACP actions, and discuss implications for health care policy. Objective To test the efficacy of the Videos on patients’ ACP/goals of care designation conversations with a health care provider.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(25 citation statements)
references
References 50 publications
0
25
0
Order By: Relevance
“…Despite high acceptable levels of satisfaction with the received treatment in both groups, the low median in QoC-EOL scores in this study reflected that the promotional leaflet alone in the control group and the stand-alone two-session ACP intervention in the intervention group might not be sufficient to improve the quality of the communication. A recent RCT also showed that video-alone intervention does not engage individuals in high-quality ACP [38]. The communication on EOL care was determined to be of low quality in this study because of the rareness of its occurrence.…”
Section: Results Of Logistic Regression On Primary Outcome and Genera...mentioning
confidence: 83%
See 1 more Smart Citation
“…Despite high acceptable levels of satisfaction with the received treatment in both groups, the low median in QoC-EOL scores in this study reflected that the promotional leaflet alone in the control group and the stand-alone two-session ACP intervention in the intervention group might not be sufficient to improve the quality of the communication. A recent RCT also showed that video-alone intervention does not engage individuals in high-quality ACP [38]. The communication on EOL care was determined to be of low quality in this study because of the rareness of its occurrence.…”
Section: Results Of Logistic Regression On Primary Outcome and Genera...mentioning
confidence: 83%
“…A lack of communication on EOL care between healthcare professionals and older adults with frailty seems to be a worldwide problem. On-going discussions and deliberation with a healthcare provider in promoting patient-physician communication on EOL care are necessary [38].…”
Section: Results Of Logistic Regression On Primary Outcome and Genera...mentioning
confidence: 99%
“…Quality of patient–physician communication: Of the 19 RCTs assessing quality of communication,24 30 37 38 48 53 55 58–69 13 (68%) showed significant improvement in the outcome 24 30 37 38 48 53 58–64. Seven of these were deemed high-quality 24 37 53 58 59 61 64.…”
Section: Resultsmentioning
confidence: 99%
“…Generally, ACP is more prevalent in developed countries, such as North America, Australia, and New Zealand, 15-18 and more widely accepted in the medical field, particularly in hospitals, communities, and nursing homes 11,15,19 . In addition to elderly patients, the ACP population comprises parents/guardians of minors with life-threatening illnesses, with the community being extended to patients with malignant tumors, Alzheimer disease, cardiovascular, and other diseases 7,19-21 . Despite the highlighted benefits of ACP in these disease states, little research has been done on the implementation of ACP by elderly AIDS patients in China.…”
mentioning
confidence: 99%
“…11,15,19 In addition to elderly patients, the ACP population comprises parents/guardians of minors with lifethreatening illnesses, with the community being extended to patients with malignant tumors, Alzheimer disease, cardiovascular, and other diseases. 7,[19][20][21] Despite the highlighted benefits of ACP in these disease states, little research has been done on the implementation of ACP by elderly AIDS patients in China.…”
mentioning
confidence: 99%